Avaliação do Desempenho do Protocolo HL7 - Farias, Daniel Gomes de Mello (2020)
Advances in information and communication technology have created the field of "health informatics", which brings together health, information technology and business. With the technological advance that emerged in the 90s and the popularization of web and internet technologies, the use of systems for health records that contain medical information of the patient, allergies, immunizations and medical history have increased. These health records bring great benefits to doctors, patients and hospitals, promoting quality care and more accurate diagnoses due to the large data collection. However, for all this data to be collected, stored and used in the best way, it is necessary that the systems of several hospitals communicate with each other and that the medical equipment sends the information to the medical records, that is, it is necessary that there is interoperability between systems. There are currently some standards that allow this interoperability such as Health Level Seven (HL 7) and textit Fast Healthcare Interoperability Resources (FHIR) that were studied in this work. They have a range of characteristics that have been compared and analyzed to define what would be the best standard to be adopted in different circumstances. Were analyzed from the size of a file to factors such as: security, practicality, scalability, integration with other standards, among other characteristics. Finally, we found that FHIR presented itself as the best current standard due to its ability to adapt to mobile devices, the Web and Internet of Things devices.